Adaptation and Validation of Cognitive Emotion Regulation Questionnaire (CERQ) in Indonesian Version - Endang Prastuti; Mareyke Maritje Wagey Tairas; Nurul Hartini (Universitas Ahmad Dahlan, 2020)
The aim of this research is to adapt and validate the Indonesian version of CERQ for adult samples. CERQ consists of nine emotional regulation strategies, with a total of 36 items. CFA (Confirmatory Factor Analysis) was used to analyse the data. The results of the study showed that based on the measurement model using CFA, CERQ totaling 36 items, through the item selection process, the remaining 17 items have high loading factor. Based on the results of the evaluation of the fit of model indicated by the parameters: chi square = 103.115 (p = 0.101), GFI = 0.895, AGFI = 0.814, CFI = 0.979, TLI = 0.967 and RMSEA = 0.044 explaining the existence of good goodness of fit. CERQ Indonesian version also has Composite Reliability (CR) in the range of 0.707-0.925 and AVE in the range of 0.786-0.927, also explaining and providing evidence of good convergent validity. The confirmed CERQ measurement model has a fit model according to empirical data. Thus, the Indonesian version of CERQ is accepted as a measure of emotion regulation, especially for young adult respondents (aged 20-40 years).Â